Bioethanol Production Using Green Algae (Chaetomorpha) As Renewable Energy - Soeprijanto Soeprijanto; Fajar Arif Widodo; Istiqfarin Istiqfarin; Nabila Fara Anindya; Putri Selly Mudyawati (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2020)
Biologically, green algae (Chaetomorpha) are a group of chlorophyll plants consisting of one or many cells and in the form of a colony. The main organic materials contain in algae for example polysaccharides, vitamins, and minerals. So far the use of algae as an industrial raw material is still relatively small. Though the chemical components containing in algae are very useful for raw materials for bioenergy. The green algae have a potential as raw material in bioethanol (C2H5OH) production as one of the alternatives and renewable energy. The purpose of these experiments was to determine the effect of a variety of concentrations of green algae on reducing sugar and bioethanol production through liquefaction, saccharification, and fermentation. Green algae flour was obtained by drying in an oven at 60°C for 24 h, then was ground. The reducing sugar was obtained by two steps, i.e., liquefaction and saccharification. In liquefaction, the algae flour was put in an Erlenmeyer 2000 ml and added by 40 mg/l CaCl2, α-amylase, and water until the slurry volume was achieved 2000 ml, then heated at 90°C-100°C for 2 h. The next step was for saccharification, in this step HCl was added in the solution to achieve a pH of 4, and glucoamylase was added, then was heated at 60°C for 4 h. The final stage was fermentation, this solution was then added with urea, NPK, and yeast, then incubated for 72 h. After fermentation, the liquid was distilled to obtain bioethanol. The results showed that the addition of enzymes with a concentration of 2% yielded reducing sugar of 64.62, 34.38, 8.46, and 1.14 g/l, with green algal concentrations of 10, 30, and 40% (w/v), respectively. The bioethanol obtained was 0, 0.81, 2.92, and 5.29%, with reducing sugar of 64.62, 34.38, 8.46, and 1.14 g/l for 0, 24, 48, and 72 h, respectively. However, the addition of enzymes with a concentration of 5% produced reducing sugar of 122.22, 55.32, 10.23, and 1.3 g/l, respectively. The bioethanol obtained was 0, 0.92, 3.71, and 8.16% for 0, 24, 48, and 72 h, respectively.  It concluded that the maximum bioethanol obtained was 8.16 % at algae concentration of 40% (w/v) for 72 h of fermentation.